Development and Validation of Chemometric Assisted UV Spectroscopic Methods for the Simultaneous Determination of Amitriptyline Hydrochloride and Propranolol Hydrochloride in Marketed Formulation - PALUR, KEERTHISIKHA; CHARAN ARCHAKAM, SREENIVASA; PATAKAM, PRIYANKA; ORUPALLI, KAVYA; YADAVALI, PADMAJA; POTHAPALA, YOGESWAR; DIVITI, RANGANAYAKULU (Asian Journal of Chemistry, 2023)
The present work discusses the development and validation of chemometric assisted UV spectroscopic methods for analyzing two drugs amitriptyline hydrochloride and propranolol hydrochloride in their marketed formulation. The developed methods are two prominent chemometric models namely, principal component regression (PCR) and partial least squares regression (PLS) on which several research articles have been published for their immense contribution in the quantification of multi-component formulations. Linearity of the UV spectroscopic method was in the concentration ranges of 3-15 μg/mL of amitriptyline hydrochloride and 5-45 μg/mL of propranolol hydrochloride. The PCR and PLS chemometric models were established by employing fourteen mixtures as a calibration set and five mixtures as a validation set and were executed in the wavelength range of 240-320 nm with data interval of 5 nm. The statistical parameters obtained from both the methods revealed their validity and hence allows their suitability for analysis in regular quality control laboratories.